On Solution of Regular Singular Initial Value Problems - Tawfiq, Luma. N. M.; Hussein, Reem. W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper devoted to the analysis of regular singular initial value problems for ordinary differential equations with a singularity of the first kind , we propose semi - analytic technique using two point osculatory interpolation to construct polynomial solution, and discussion behavior of the solution in the neighborhood of the regular singular points and its numerical approximation, two examples are presented to demonstrate the applicability and efficiency of the methods. Finally , we discuss behavior of the solution in the neighborhood of the singularity point which appears to perform satisfactorily for singular problems.